L LONGITUDINAL POLICY BUDGETING DALAM PENERAPAN GOOD GOVERNANCE DI SUMATERA BARAT - Bobi Rizki Ananda; Ria Ariany; Bunga Bhakti Tama (Jurnal Administrasi Publik dan Pemerintahan, 2026)
The purpose of this study is to examine and describe regional financial management in support of good governance principles in West Sumatra Province. A longitudinal approach is used to track the development and effectiveness of budgeting policies over time, as well as their impact on transparency, accountability, participation, and efficiency of local government. This study utilizes secondary data from regional financial reports, development planning documents, and budget implementation evaluations over the past several years. The findings indicate that the implementation of sustainable budgeting policies can improve the quality of regional financial governance, strengthen public oversight, and encourage public participation in the decision-making process. However, challenges related to human resource capacity and inter-agency coordination still require attention to strengthen the implementation of good governance comprehensively, and to address changing budget policies.